Pengaruh Literasi Keuangan dan Pembayaran Digital Terhadap Kinerja UMKM Melalui Inovasi Sebagai Variabel Mediasi di Kota Palangka Raya - Eko Agus Nadhif; Solikah Nurwati; Eka Indra Kusuma; Vira Saskia (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the influence of financial literacy and digital payments on the performance of MSMEs through innovation as a mediating variable in Palangka Raya City. The study used a quantitative approach with an explanatory design. A total of 155 respondents were selected using the Slovin formula and purposive sampling technique. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method using SmartPLS 4. The results showed that financial literacy and digital payments have a positive and significant effect on innovation and MSME performance. The results also revealed that innovation has a significant influence on MSME performance and is a mediating mechanism between financial literacy, digital payments, and MSME performance. These findings emphasize the importance of increasing financial capacity and adopting digital payment technology in encouraging innovation and improving business performance.